Urban and rural differences in frequency of fruit, vegetable, and soft drink consumption among 6–9‐year‐old children from 19 countries from the WHO European region - Heinen, Mirjam M. (2021)
In order to address the paucity of evidence on the association between childhood eating habits and urbanization, this cross-sectional study describes urban–rural differences in frequency of fruit, vegetable, and soft drink consumption in 123,100 children aged 6–9 years from 19 countries participating in the fourth round (2015-2017) of the WHO European Childhood Obesity Surveillance Initiative (COSI). Children's parents/caregivers completed food-frequency questionnaires. A multivariate multilevel logistic regression analysis was performed and revealed wide variability among countries and within macroregions for all indicators. The percentage of children attending rural schools ranged from 3% in Turkey to 70% in Turkmenistan. The prevalence of less healthy eating habits was high, with between 30–80% and 30–90% children not eating fruit or vegetables daily, respectively, and up to 45% consuming soft drinks on >3 days a week. For less than one third of the countries, children attending rural schools had higher odds (OR-range: 1.1–2.1) for not eating fruit or vegetables daily or consuming soft drinks >3 days a week compared to children attending urban schools. For the remainder of the countries no significant associations were observed. Both population-based interventions and policy strategies are necessary to improve access to healthy foods and increase healthy eating behaviors among children.